Explaining the challenges faced by nursing students in clinical learning environments during the post-COVID era: a qualitative content analysis - Zeinab Jokar; Mostafa Bijani; Hajar Haghshenas (BMC Research Notes)
Abstract Objectives The COVID-19 pandemic precipitated unprecedented disruptions across global healthcare systems, with nursing education being particularly affected. In addition to the challenges encountered during the height of the crisis, the aftermath of the pandemic has continued to impose significant difficulties on nursing students, especially within clinical learning environments. Despite the breadth of emerging literature, a notable gap persists in studies explicitly examining the post-pandemic experiences of nursing students in these settings. Moreover, the present study is a qualitative study with the content analysis in Iran from October 2024 to February 2025. Twenty- two nursing students participated in this study. Data were collected from individual, and semi-structured interviews. Data analysis was conducted using the qualitative content analysis method proposed by Graneheim and Lundman (2004). Results The analysis yielded three overarching themes, each encompassing specific subthemes: (1) lack of clinical competence (insufficient clinical knowledge, deficiency in clinical skills, and poor clinical judgment.) (2), psychological challenges (the quagmire of hopelessness, emotional exhaustion, and lack of self-efficacy) and (3) disruption in professional interactions (lack of mutual respect and absence of a team-oriented spirit). Clinical trial number Not applicable.